A qualitative comparison of needles and insulin pump use in children with type 1 diabetes. (September 2018) - Ferrari, Madeleine; McIlwain, Doris JF; Ambler, Geoffrey
Managing type 1 diabetes mellitus is an ongoing and challenging process; we investigated children's experience of different treatment regimens. Interviews with 17 children (7–15 years) at two time points were analysed using the grounded theory approach. Illness phase and treatment regimen shaped how bodily cues were interpreted. Insulin pump therapy allowed children to listen to and trust their bodily cues rather than override. Shame was a barrier to support engagement. Different internalised and externalised views of type 1 diabetes mellitus emerged. Overall, children were insightful experts of their own experiences. Recommendations for psychological interventions would benefit from empirical testing.